Design and fabrication of dioxyphenylcoumarin substituted cyclotriphosphazene compounds photodiodes - Elgazzar, Elsayed; Dere, Ayşegül; Özen, Furkan; Koran, Kenan; Al-sehemi, Abdullah G.; Al-ghamdi, Ahmed A.; Görgülü, Ahmet Orhan; El-tantawy, F.; Yakuphanoğlu, Fahrettin (My University, 2017)
The present study introduces cyclotriphosphazene compounds substituted by dioxyphenylcoumarin as a photodiode application. Firstly, 7,8-dihydroxy-3-(3-methylphenyl)coumarin (1b) has been obtained by conventional as well as microwave assisted methods. Novel optoelectronic device characteristics for both mono and disubstituted dioxyphenylcoumarin bearing cyclotriphosphazene compounds (HCP-2 and HCP-4) have been synthesized from the reactions of cyclotriphosphazene containing dioxybiphenyl (HCP-1 and HCP-3) with compound 1b, respectively. The structures of compounds HCP 1–4 were identified by using elemental analysis, 1H, 13C-APT, 31P NMR and 2D HETCOR NMR and FT-IR spectroscopy methods. The Al/HCP-2/p-Si/Al and Al/HCP-4/-p-Si/Al photodiodes properties have been investigated from current-voltage (I?V) and capacitance-voltage (C?V) measurements. The electrical parameters of the prepared diodes such as ideality factor n and series resistance Rs were investigated in dark and at room temperature from (I?V) curve and Nord's method. As can be seen, the Al/HCP-2/p-Si/Al diode of high rectification ratio RR and with ideality factor greater than unity. The influence of light illuminations on the diode shows that the device can be used as photodiode with good efficiency. The barrier height ?b and series resistance Rs have been calculated from the capacitance-voltage (C?V)and conductance-voltage (G?V) measurements under various applied frequencies from 10 kHz to 1 MHz. the high difference in the results of barrier height obtained from I-V and C-V calculations confirm the influence of series resistance and localized states on transport of charge carriers and the photodiode performance.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Photodiode; Sensor; Cyclotriphosphazene; Dioxycoumarin-phosphazene